2011
DOI: 10.1088/0957-4484/22/8/085301
|View full text |Cite
|
Sign up to set email alerts
|

Electron-beam-induced deposition and post-treatment processes to locally generate clean titanium oxide nanostructures on Si(100)

Abstract: We have investigated the lithographic generation of TiO(x) nanostructures on Si(100) via electron-beam-induced deposition (EBID) of titanium tetraisopropoxide (TTIP) in ultra-high vacuum (UHV) by scanning electron microscopy (SEM) and local Auger electron spectroscopy (AES). In addition, the fabricated nanostructures were also characterized ex situ via atomic force microscopy (AFM) under ambient conditions. In EBID, a highly focused electron beam is used to locally decompose precursor molecules and thereby to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…From this perspective FEBID will have to move towards a better microscopic understanding of all relevant processes in a controlled environment, i.e., under UHV conditions and augmented by a selection of surface science analysis techniques. One may hope that results from research under these much better controlled conditions (see e.g., [6566]) will also be helpful to optimize FEBID processes in the standard SEM environment where it is already today a most attractive technique for structure formation on the nanometer scale.…”
Section: Resultsmentioning
confidence: 99%
“…From this perspective FEBID will have to move towards a better microscopic understanding of all relevant processes in a controlled environment, i.e., under UHV conditions and augmented by a selection of surface science analysis techniques. One may hope that results from research under these much better controlled conditions (see e.g., [6566]) will also be helpful to optimize FEBID processes in the standard SEM environment where it is already today a most attractive technique for structure formation on the nanometer scale.…”
Section: Resultsmentioning
confidence: 99%
“…Hoffmann et al demonstrated the fabrication of high refractive index materials for photonic bandgap structures [13] and Mitchell and Hu reported on the generation of μm-scaled, titanium and oxygencontaining area deposits on gallium arsenide [14,15]. In a previous study we found that with TTIP, even when applied under UHV conditions, the deposits contained significant amounts of carbon, besides the targeted materials titanium and oxygen [16]. The carbon contamination was traced back to the carbon-containing precursor itself.…”
Section: Introductionmentioning
confidence: 91%
“…FEBID is a versatile technique for nanoprototyping and research, as it permits the deposition of material in a variety of shapes with high spatial resolution. Moreover, it is also possible to deposit oxides [ 10 ] and, by co-injecting different precursors, alloy materials with tunable properties [ 11 ]. A review of the application of the technique to the deposition of magnetic nanostructures has recently been published [ 12 ].…”
Section: Introductionmentioning
confidence: 99%